ACPA and RF as predictors of sustained clinical remission in patients with rheumatoid arthritis: data from the Ontario Best practices Research Initiative (OBRI). Issue 2 (5th November 2018) - Pope, Janet E; Movahedi, Mohammad; Rampakakis, Emmanouil; Cesta, Angela; Sampalis, John S; Keystone, Edward; Thorne, Carter; Bombardier, Claire
Abstract : Objective(s): This study evaluated the interaction of anticitrullinated protein antibody (ACPA) and rheumatoid factor (RF) in predicting sustained clinical response in an observational registry of patients with rheumatoid arthritis (RA) followed in routine practice. Methods: Patients with RA enrolled in the Ontario Best Practices Research Initiative registry, with ≥1 swollen joint, autoantibody information and ≥1 follow-up assessment were included. Sustained clinical remission was defined as Clinical Disease Activity Index (CDAI) ≤2.8 in at least two sequential visits separated by 3–12 months. Time to sustained remission was assessed using cumulative incidence curves and multivariate cox regression. Results: Among 3251 patients in the registry, 970 were included, of whom 262 (27%) were ACPA neg /RF neg, 60 (6.2%) ACPA pos /RF neg, 117 (12.1%) ACPA neg /RF pos and 531 (54.7%) ACPA pos /RF pos at baseline. Significant between group differences were observed in age (p=0.02), CDAI (p=0.03), tender joint count (p=0.02) and Health Assessment Questionnaire (p=0.002), with ACPA pos patients being youngest with lowest disease activity and disability. No difference in biologic use was found between groups (20.2% of patients). Over a mean follow-up of 3 years, sustained remission was achieved by 43.5% of ACPA pos /RF pos patients, 43.3% of ACPA pos /RF neg patients, 31.6 % of ACPA neg /RF pos patients and 32.4% of ACPA neg /RF neg patients (p=0.01). Significant differences were observed in CDAI improvement based on ACPA and RF status where ACPA pos /RF pos had a shorter time to achieving sustained remission (HR 1.30; 95% CI 1.01 to 1.67) and experienced significantly higher improvements compared with ACPA neg /RF neg patients. Conclusion(s): Combined ACPA and RF positivity were associated with improved and faster response to antirheumatic medications in patients with RA.